2021
DOI: 10.1007/s10741-021-10168-9
|View full text |Cite
|
Sign up to set email alerts
|

Advanced airway management and respiratory care in decompensated pulmonary hypertension

Abstract: Meticulous risk stratification is essential when considering intubation of a patient with decompensated pulmonary hypertension (dPH). It is paramount to understand both the pathophysiology of dPH (and associated right ventricular failure) and the complications related to a high-risk intubation before attempting the procedure. There are few recommendations in this area and the literature, guiding these recommendations, is limited to expert opinion and very few case reports/case series. This review will discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Of relevance to PH predisposed cohort, HFNC by avoiding positive pressure ventilation not only avoids pulmonary vessel compression but also circumvents hypoxic pulmonary vasoconstriction that decrescents right ventricular preload as well. 10 Even from a strict cardiac perioperative perspective, Kumar et al very recently proposed role of HFNC in postoperative acyanotic CHD patients, where the authors reported improvement in postextubation partial pressure of oxygen/fraction of inspired oxygen concentration (P a O 2 /FiO 2 ). 11 While our patients were postoperative adults with congenital heart disease patient akin to the Kumar et al study, 11 the additional attributes such as a previous history of COVID-19 infection, collapsed lung lobe, intraoperative PH crisis, and recent tapering of iNO implied an accentuated risk in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance to PH predisposed cohort, HFNC by avoiding positive pressure ventilation not only avoids pulmonary vessel compression but also circumvents hypoxic pulmonary vasoconstriction that decrescents right ventricular preload as well. 10 Even from a strict cardiac perioperative perspective, Kumar et al very recently proposed role of HFNC in postoperative acyanotic CHD patients, where the authors reported improvement in postextubation partial pressure of oxygen/fraction of inspired oxygen concentration (P a O 2 /FiO 2 ). 11 While our patients were postoperative adults with congenital heart disease patient akin to the Kumar et al study, 11 the additional attributes such as a previous history of COVID-19 infection, collapsed lung lobe, intraoperative PH crisis, and recent tapering of iNO implied an accentuated risk in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…Of relevance to PH predisposed cohort, HFNC by avoiding positive pressure ventilation not only avoids pulmonary vessel compression but also circumvents hypoxic pulmonary vasoconstriction that decrescents right ventricular (RV) preload as well. 10 Even from a strict cardiac perioperative perspective, Kumar et al very recently proposed role of HFNC in postoperative acyanotic CHD patients, where the authors reported improvement in postextubation partial pressure of oxygen/fraction of inspired oxygen concentration (PaO 2 /FiO 2 ). 11 While our patients were postoperative adult CHD patient akin to the Kumar et al study, 11 the additional attributes such as a previous history of COVID-19 infection, collapsed lung lobe, intraoperative PH crisis, and recent tapering of iNO, implied an accentuated risk in our setting.…”
Section: Discussionmentioning
confidence: 99%
“…Positive end-expiratory pressure (PEEP) can improve oxygenation but may increase alveolar distention, worsen pulmonary vascular resistance, and increase RV afterload. 7,8…”
Section: Airway Management In Rvfmentioning
confidence: 99%